Implementasi Taqwim Standar Indonesia sebagai Pemersatu Kalender Masyarakat Indonesia - Adam Firmansyah Ahmad; Fatmawati, Azizah; Siti Tatmainul Qulub (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2022)
Indonesia is famous for its diversity ranging from culture, religion, ethnicity and others. Including the calendar system owned by each tribe or local community. In Indonesia itself for the calendar calendar system that is known in general, namely the Samsiyah calendar system (AD) and the Qomariyah year (Hijri). Almost every tribe or community in every region in Indonesia has their own local calendar or calendar according to their beliefs. Due to the existence of these various calendars, the Government is trying to unify these various types of calendars through the Indonesian Standard Taqwin, where the method or criteria used are the Imkan al-Rukyat criteria or the Visibility of the Hilal MABIMS. Although there is no obligation to comply with one regulation, namely regarding the use of one main calendar, this effort is intended to harmonize the use of calendars in Indonesia.